Comparison of Content and Psychometric Properties of Malnutrition Outcome Measures: A Systematic Review - Līga Savicka; Santa Salaka; Guna Bērziņa (Medical Journals Sweden, 2022)
Objective: To determine the most-often used outcome measures for malnutrition risk and malnutrition, analyse outcome measure content, and assess psychometric properties. Methods: MEDLINE, SAGE Journals, Web of Science, SCOPUS, ProQuest and Science Direct databases were searched to identify outcome measures. Outcome measure content was compared using the International Classification of Functioning Disability and Health (ICF). Psychometric properties were also systematically searched and compared. This review was prepared according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: A total of 1,311 studies met the inclusion criteria. The most-often used outcome measures for detecting malnutrition or its risk overall were: body mass index (590), albumin (469), Mini Nutritional Assessment (312), haemoglobin (251), and Subjective Global Assessment (139). The most psychometrically sound outcome measure was Mini Nutritional Assessment, but the most comprehensive measure, covering the most ICF categories, was Patient-Generated Subjective Global Assessment, with a total of 58 meaningful concepts. Conclusion: The results provide an insight into the content and psychometric quality of malnutrition risk and malnutrition outcome measures. There was some variation between the way reviewers linked meaningful concepts to ICF, and literature gaps were identified regarding psychometric properties. These results can be used to help select the most appropriate malnutrition outcome measure. LAY ABSTRACT Malnutrition leads to a decline in physical and mental functioning, as well as activity limitations, which can result in poor disease outcomes and reduced quality of life. Early identification of malnutrition depends on choosing the most appropriate diagnostic method. This article systematically analyses the outcome measures most commonly used in research for detecting malnutrition risk and malnutrition in adults. The content of the most common outcome measures was analysed using the International Classification of Functioning Disability and Health (ICF). Linking rules, and the psychometric properties of the measures were systematically searched, analysed according to an already established framework, and compared.